Summary Islamic Ethics in Business Management, Evidence in North Sumatra - Budi Harianto; Syafril Syafril (Journal of Management and Business Innovations, 2022)
The Qur'an is a holy book revealed to Allah SWT that provides benefits for certainty and belief, written in the holy book from the beginning of Surah al-Fatihah to the end of Surah An-Naas (Mushaf Usmany), ordered to be delivered to his people, as a guide and the demands of life for mankind. The Qur'an not only encourages Muslims to trade, but also the Qur'an frames that trade is carried out by upholding moral values. Honesty, trust, sincerity and fairness are examples of trade ethics that will never rot with time. This paper focuses on the importance of ethics Islam in trading. By paying attention to about 100 objects of Muslim entrepreneurs in various business lines in North Sumatra, it is obtained several Islamic ethics in business management which tend to be often implemented including Unity, Equilibrium, Free Will, Responsibility and Benevolence.Keywords: Business management., islamic ethics